Polycrystalline metal oxides with enriched grain boundaries
Patent Information
- Application Number
- JP2024203449
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-01-17
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2039-10-23
Smart Images

Figure 2025026975000001_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application is dependent upon and claims priority from U.S. patent application Ser. No. 16 / 250,615, filed Jan. 17, 2019, U.S. patent application Ser. No. 16 / 250,762, filed Jan. 17, 2019, and U.S. patent application Ser. No. 16 / 250,622, filed Jan. 17, 2019, the entire contents of each of which are incorporated herein by reference.
[0002] FIELD OF THEINVENTION Polycrystalline metal oxide particles, methods for their manufacture, and electrochemical cells or batteries containing them are disclosed.
[0003] 2. Background of the Invention Materials based on layered-structured lithium nickel oxide (LiNiO2) have been developed for lithium-ion battery cathodes because they generally have lower cost, higher capacity, and higher rated capacity than the historically dominant LiCoO2 cathode material. However, pure LiNiO2 materials exhibit poor electrochemical stability and cycling performance. To address this, non-nickel element additives have been formulated into LiNiO2 to stabilize the structure and improve cycling performance, but this typically comes at the expense of discharge capacity. With the demand for energy density increasing, research has focused on optimizing and reducing these non-nickel additives to obtain the capacity of high-Ni materials while maintaining cycling performance.
[0004] Thus, new materials are needed to address the demand for high capacity materials with long cycle life. The materials and methods of forming such materials provided herein address this demand by maintaining high capacity over long cycle life.
[0005] Summary of the Invention The following summary is provided to facilitate understanding of some of the innovative features unique to the present disclosure and is not intended to be a complete description. A full understanding of the various aspects of the present disclosure can be obtained by taking the entire specification, claims, drawings, and abstract as a whole.
[0006] Secondary particles are provided which have been found to exhibit significantly reduced impedance growth when used as cathode electrochemical active materials in Li-ion secondary batteries. By selectively enriching the grain boundaries between the crystallites of the secondary particles with a combination of Co and Al, improved impedance profiles can be achieved, and it has been found that these improved impedance profiles are achieved in many compositionally distinct electrochemically active materials.
[0007] Thus, a particle is provided that includes a plurality of crystallites that includes a first composition containing lithium, nickel, and oxygen, and a grain boundary between adjacent crystallites of the plurality of crystallites that includes a second composition having a layered α-NaFeO2 type structure, a cubic structure, a spinel structure, or a combination thereof, wherein the concentration of aluminum at the grain boundary is higher than the concentration of aluminum in the crystallites, and the concentration of cobalt at the grain boundary is higher than the concentration of cobalt in the crystallites. In some embodiments, the grain boundary Al enrichment is non-uniform, incomplete, or not achieved, but it has been found that when the manufacturing process provided herein is utilized, Al grain boundary enrichment can be achieved, and optionally Co and Al grain boundary enrichment can be achieved. Thus, in some embodiments, Al is substantially uniformly distributed throughout the plurality of particles.
[0008] In some embodiments, the amount of Al at the grain boundaries is 0.01 at% to 10 at% of the total amount of transition metals in the remainder of the secondary particles. Optionally, the amount of Co at the grain boundaries is 0 at% to 10 at% of the total amount of transition metals in the remainder of the secondary particles, and optionally is 0.1 at% to 10 at% of the total amount of transition metals in the remainder of the secondary particles. Optionally, the amount of Al at the grain boundaries is 0.01 at% to 5 at% of the total amount of transition metals in the remainder of the secondary particles, and the amount of Co at the grain boundaries is 0.01 at% to 10 at% of the total amount of transition metals in the remainder of the secondary particles. Optionally, the amount of Aluminum at the grain boundaries is equal to or less than the amount of Co at the grain boundaries.
[0009] In some embodiments, the plurality of crystallites has an α-NaFeO 2 -type layered structure, a cubic structure, a spinel structure, or a combination thereof.
[0010] Optionally, the first composition, the second composition, or both, in any of the above or other embodiments, comprises Li 1+x MO 2+y wherein: -0.1≦x≦0.3, -0.3≦y≦0.3, M comprises 10 atomic percent or more of nickel. Optionally, M comprises 75 at% or more of nickel. Optionally, the overall grain boundary comprises cobalt in an amount between about 2 at% and about 99 at% and aluminum in an amount between about 2 at% and about 99 at%. Optionally, in the first composition, the second composition, or both, M further comprises an additional metal, the additional metal being present in an amount between about 1 at% and about 90 at%, the additional metal being selected from the group consisting of Mg, Sr, Co, Al, Ca, Cu, Zn, Mn, V, Ba, Zr, Ti, Nb, Ta, Cr, Fe, Mo, W, Hf, B, and any combination thereof, whereby the one or more additional elements are optionally present in the Li layer, the M layer, or both.
[0011] Optionally, the crystallites include cobalt, and the cobalt concentration ranges from 1 at% to about 50 at%, optionally from 1 at% to about 15 at%. In some embodiments, the crystallites include Mn present in an amount of about 1 at% to about 60 at%, and the grain boundaries include Mn present in an amount of about 1 at% to about 60 at%. In other embodiments, the grain boundaries include Ni, Co, and Al. Optionally, the concentration of Ni at the grain boundaries is greater than 75 at%.
[0012] Some embodiments of the particle include an outer coating on the surface of the particle, the outer coating comprising an oxide of one or more elements selected from Al, Zr, Y, Co, Ni, Mg, and Li; a fluoride comprising one or more elements selected from Al, Zr, and Li; a carbonate comprising one or more elements selected from Al, Co, Ni, Mn, and Li; or a phosphate or sulfate comprising one or more elements selected from Al and Li.
[0013] In another aspect provided herein, Li 1+x MO 2+y wherein -0.1≦x≦0.3, -0.3≦y≦0.3, and M comprises 80 atomic percent or more of nickel; and grain boundaries between adjacent crystallites of the plurality of crystallites, optionally comprising Li 1+x MO 2+yand grain boundaries comprising a second composition having a layered α-NaFeO2-type structure, a cubic structure, or a combination thereof, wherein the concentration of aluminum at the grain boundaries is greater than the concentration of aluminum in the crystallites, and optionally the concentration of cobalt at the grain boundaries is greater than the concentration of cobalt in the crystallites, and the aluminum is substantially uniformly distributed throughout the grain boundaries. Optionally, the concentration of cobalt in the crystallites is about 0 to about 17 atomic percent of M in the first composition, and the amount of cobalt at the grain boundaries is about 0 to about 10 atomic percent of M in the crystallites. Optionally, M further comprises one or more elements selected from the group consisting of Na, K, Al, Mg, Co, Mn, Ca, Sr, Ba, Zn, Ti, Zr, Y, Cr, Mo, Fe, V, Si, Ga, and B, wherein the one or more elements are present in the Li layer, the M layer, or both of the crystallites. Optionally, M comprises 90 percent or greater atomic percent of nickel.
[0014] An electrochemical cell is also provided. The electrochemical cell includes a cathode active material. The cathode active material optionally includes any of the particles described above or elsewhere herein. The electrochemical cell is optionally characterized by an impedance increase at 4.2V of less than 100% over 100 cycles at 45°C, and optionally less than 100% over 200 cycles at 45°C.
[0015] Also provided is an electrochemical cell, optionally a secondary battery, optionally a lithium-ion secondary battery, comprising an anode, an electrolyte, and a cathode, the cathode comprising an electrochemically active cathode active material comprising a plurality of particles comprising a plurality of crystallites, each of the crystallites comprising a first composition containing lithium, nickel, and oxygen, and grain boundaries between adjacent crystallites of the plurality of crystallites, the grain boundaries comprising a second composition having a layered α-NaFeO2-type structure, a cubic structure, a spinel structure, or a combination thereof, the electrochemically active cathode active material having an initial discharge capacity of 180 mAh / g or greater and an impedance increase at 4.2 V of less than 50% at 45° C. over 100 cycles. The electrochemical cell is optionally characterized by an impedance increase at 50% state of charge of less than 50% over 200 cycles at 45° C., and optionally less than 120% over 200 cycles at 45° C. In some embodiments, the electrochemical cell is characterized by an impedance increase of less than 50% over 200 cycles at 45° C. at 50% state of charge. Optionally, each of the crystallites comprises lithium, nickel, cobalt, and oxygen. Optionally, the crystallites comprise Al, Mn, Mg, or combinations thereof.
[0016] Optionally, the first composition, the second composition, or both, in any of the above or other embodiments, comprises Li 1+x MO 2+y wherein: -0.95≦x≦0.3, -0.3≦y≦0.3, and M comprises 80 atomic percent or more of nickel. Optionally, in the first composition, M comprises 75 at% or more of nickel relative to the total transition metals in the first composition. In the second composition, M is optionally 90 at% or less relative to the total transition metals in the second composition. Optionally, the overall grain boundary comprises cobalt in an amount between about 2 at% and about 99 at% and aluminum in an amount between about 2 at% and about 99 at%. Optionally, in the first composition, the second composition, or both, M further comprises an additional metal, the additional metal being present in an amount of about 1 at% to about 90 at% based on total metals in the first composition or the second composition, respectively, and the additional metal being selected from the group consisting of Mg, Sr, Co, Al, Ca, Cu, Zn, Mn, V, Ba, Zr, Ti, Nb, Ta, Cr, Fe, Mo, W, Hf, B, and any combination thereof, whereby the one or more additional elements are optionally present in the Li layer, the M layer, or both.
[0017] Optionally, the crystallites include cobalt, with a cobalt concentration ranging from 1 at% to about 50 at%, and optionally ranging from 1 at% to about 15 at%, relative to the total transition metals of the first composition. In some embodiments, the crystallites include Mn present in an amount of about 1 at% to about 60 at%, and the grain boundaries include Mn present in an amount of about 1 at% to about 60 at%. In other embodiments, the grain boundaries include Ni, Co, and Al. Optionally, the concentration of Ni in the grain boundaries is greater than 75 at%.
[0018] The embodiments set forth in the drawings are illustrative and exemplary in nature and are not intended to limit the subject matter defined by the claims. The following detailed description of exemplary embodiments can be understood when read in conjunction with the following drawings. [Brief description of the drawings]
[0019] [Figure 1] FIG. 1 is a schematic perspective view of a cross-section of a secondary particle provided in accordance with some embodiments described herein. [Diagram 2]FIG. 1 illustrates the capacity fade of a full cell using secondary particles according to certain embodiments provided herein. [Diagram 3] FIG. 1 illustrates the impedance increase of a full cell using secondary particles according to certain embodiments provided herein. [Figure 4] FIG. 13 shows EDS mapping of secondary particles provided herein with Al alone or Al in the presence of Co concentrated at the grain boundaries. [Diagram 5] 1 is a scanning transmission electron micrograph (STEM) image of a small area of a secondary particle according to an embodiment provided herein containing multiple crystallites produced by enriching the grain boundaries with both 1.9 at.% Al and 4 at.% Co, showing where three EDS spot analyses were performed. [Figure 6] FIG. 6 is an EDS spectrum of the three spots shown in FIG. 5. [Figure 7] 1 is a STEM image of a small area of a secondary particle according to an embodiment provided herein containing multiple crystallites produced by concentrating 1.9 at. % Al at the grain boundaries in the absence of Co in the processing solution, showing where two EDS spot analyses were performed. [Figure 8] FIG. 8 is an EDS spectrum of the three spots shown in FIG. 7. [Figure 9] FIG. 13 shows EDS mapping of secondary particles provided herein produced by non-aqueous processing for grain boundary enrichment of the raw particles during production using Al alone or Al with the presence of Co in the processing solution. [Figure 10] FIG. 13 shows the cycling capacity fade for cells formed with cathodes incorporating enriched active material grain boundaries according to embodiments provided herein, fabricated with 0 at.% Al in the treatment solution and 0.5 at.% Al in the treatment solution, and their dependence on added Co content. [Figure 11]FIG. 13 illustrates the impedance increase for cells formed with cathodes incorporating enriched active material grain boundaries according to embodiments provided herein fabricated with 0 at.% Al in the treatment solution and 0.5 at.% Al in the treatment solution, as well as their dependence on additional Co content. [Figure 12] FIG. 13 shows the synergistic benefits observed by incorporating Al in addition to Co enrichment at grain boundaries. [Figure 13] FIG. 1 illustrates the cycling capacity fade and impedance increase of cells having grain boundary enriched cathode materials according to some embodiments provided herein using a 3 at.% Co process with various Al levels. [Figure 14] FIG. 2 illustrates the impedance increase at various Al / Co enriched atomic percentage ratios of cathode active materials provided herein, according to some embodiments. [Figure 15] FIG. 13 shows the results of STEM and EDS analysis of three spots in a small region of a secondary particle of an NCA produced as provided herein, which is a grain boundary enriched in Al in the presence of Co. [Figure 16] FIG. 13 shows the cycling capacity fade of cells formed with cathodes containing a control or grain boundary enriched NCA active material according to embodiments provided herein. [Figure 17] FIG. 13 shows the impedance increase for cells formed with cathodes containing a control or grain boundary enriched NCA active material according to embodiments provided herein. [Figure 18] FIG. 13 shows the cycling capacity fade of cells formed with cathodes containing a control or grain boundary enriched NCM active material according to embodiments provided herein. [Figure 19] FIG. 13 shows the impedance increase for cells formed with cathodes containing a control or grain boundary enriched NCM active material according to embodiments provided herein.
[0020] Detailed Description The following description is merely exemplary in nature and is not intended in any way to limit the scope of the disclosure or its application or use, which may of course vary. Materials and processes are described in conjunction with non-limiting definitions and terms contained herein. These definitions and terms are not intended to serve as limitations on the scope or practice of the present disclosure, but are presented for illustrative and explanatory purposes only. Although a process or composition is described as a sequence of individual steps or using specific materials, it is understood that the steps or materials may be interchangeable such that the description of the present invention may include multiple parts or steps arranged in many ways so that it can be easily understood by those skilled in the art.
[0021] Terms such as "first," "second," "third," and the like may be used herein to describe various elements, components, regions, layers, and / or portions, but it will be understood that these elements, components, regions, layers, and / or portions should not be limited by these terms. These terms are used only to distinguish one element, component, region, layer, or portion from another element, component, region, layer, or portion. Thus, unless otherwise stated, a "first element," "component," "region," "layer," or "portion" described below can be referred to as a second (or another) element, component, region, layer, or portion without departing from the teachings of this specification.
[0022] The terms used herein are for the purpose of describing particular aspects only and are not intended to be limiting. As used herein, the singular forms "a," "an," and "the" are intended to include the plural, including "at least one," unless the content clearly dictates otherwise. "Or" means "and / or." As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items. As used herein, the terms "comprises" and / or "comprising," or "includes" and / or "including" specify the presence of the stated features, regions, integers, steps, operations, elements, and / or components, but are further understood not to preclude the presence or addition of one or more other features, regions, integers, steps, operations, elements, components, and / or groups thereof. The term "or combinations thereof" refers to combinations including at least one of the aforementioned elements.
[0023] Unless otherwise specified, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by those skilled in the art to which this disclosure belongs. Furthermore, terms as defined in commonly used dictionaries should be interpreted to have a meaning consistent with their meaning in the context of the relevant art and this disclosure, and should not be interpreted in an ideal or overly formal sense unless expressly defined in this specification.
[0024] Ni-based layered materials of the LiMO2 type are dense polycrystalline aggregates of primary crystals. They are typically produced using standard solid-state processes at temperatures ranging from 600 °C to 900 °C, starting from various precursor materials. The precursor materials are typically transition metal hydroxides (M(OH)2), lithium precursors (e.g. LiOH or Li2CO3), or inorganic precursors for other dopants (e.g. hydroxides, carbonates, nitrates). During heating of the precursor mixture, polycrystalline LiMO2 is formed with the release of gases such as H2O, CO2, or NO2.
[0025] Sintering with suitable precursors under suitable conditions results in the formation of multiple primary crystallites that form into larger secondary particles that can function as electrochemically active materials. It has previously been found that the regions between these primary crystallites, the grain boundaries, can be selectively enriched with Co as seen in U.S. Pat. No. 9,209,455. In this disclosure, the inventors have found that even greater improvements can be achieved by replacing some of the enriched Co at the grain boundaries with Al to further reduce impedance increase and improve cycle life. It is understood that the synergistic relationship between Co and Al at the grain boundaries, particularly Co levels between 2 mole percent Co and 5 mole percent Co (relative to the total M content in the crystallites) combined with lower relative levels of Al, significantly reduces impedance increase and improves cycle life of electrochemical cells using this material as a cathode active material.
[0026] Thus, the present disclosure provides improved electrochemical active materials, such as those suitable for use in the positive electrodes (cathodes) of Li-ion secondary batteries, that exhibit reduced rates of impedance increase and / or capacity fade during battery charge / discharge cycling compared to conventional materials. Also provided are various methods for achieving high discharge capacity cathode active materials that exhibit reduced impedance increase and capacity fade when cycled compared to the same materials but without Co and Al enrichment at the grain boundaries.
[0027] The polycrystalline layered lithiated metal oxides provided herein exhibit enhanced electrochemical performance and stability. The compositions prevent the performance degradation of electrochemically cycled Ni-containing polycrystalline LiMO2-based materials by reducing the impedance increase rate during electrochemical cycling, while maintaining other desired end-use article properties, such as the electrochemical capacity of rechargeable lithium-ion cathodes made from such layered metal oxides. Such Co and Al enriched grain boundary materials can be easily produced by calcining a compact formulation containing LiOH and a precursor hydroxide or carbonate to form particles with defined grain boundaries, and then enriching the grain boundaries with a combination of Co and Al, so that the resulting particles have grain boundaries, with higher concentrations of Co and Al at the grain boundaries than before enrichment, and optionally higher than within the primary crystallites, and their outer surfaces define the edges of the grain boundaries in the secondary particles.
[0028] Thus, compositions, systems, and methods are provided for making and using polycrystalline layered structure lithiated metal oxides having Co and Al enriched grain boundaries in lithium ion secondary batteries as a means to achieve high initial discharge capacity and low impedance increase during cycling, thereby overcoming previous challenges of high nickel formulations that can also have high discharge capacity (e.g., >205 mAh / g at C / 20).
[0029] The materials provided include particles that include a plurality of crystallites, each of which includes a first composition. Particles formed from a plurality of crystallites may be referred to as secondary particles. The particles provided herein are uniquely tailored to have grain boundaries between the primary crystallites. The combination of Co and Al, and optionally specific relative concentrations of Co and Al, enriched after formation of these grain boundaries, results in particles that reduce impedance increase during cycling and improve performance and cycle life of cells containing the particles as a cathode component.
[0030] It is understood that the particles include grain boundaries formed from or including the second composition, e.g., the concentration of cobalt and aluminum at the grain boundaries is higher than the concentration of cobalt and aluminum in the primary crystallites adjacent thereto. The concentration of Co and Al at the grain boundaries is optionally higher than the average concentration of Co and Al in the adjacent crystallites, on average. The materials provided herein are optionally relatively uniform in Co and / or Al concentration (if any is present) within the crystallites. Whether uniform or not, the concentration of Co and Al at the grain boundaries is higher than the average concentration of Co and Al, separately or combined, in the adjacent crystallites. Optionally, the materials provided include an additional outer coating layer that may be disposed on the outer surface of the secondary particles to obtain coated secondary particles.
[0031] In some embodiments of the particles provided herein, the first composition has a composition Li 1+x MO 2+yand optionally a cell or battery is formed therefrom, wherein -0.1≦x≦0.3 and -0.3≦y≦0.3. In some embodiments, x is -0.1, optionally 0, optionally 0.1, optionally 0.2, or optionally 0.3. Optionally, x is -0.10 or more, -0.09 or more, -0.08 or more, -0.07 or more, -0.06 or more, -0.05 or more, -0.04 or more, -0.03 or more, -0.02 or more, -0.01 or more, 0.00 or more, 0.01 or more, 0.02 or more, 0.03 or more, 0.04 or more, 0.05 or more, 0.06 or more, 0.07 or more, 0.08 or more, 0.0 9 or more, 0.10 or more, 0.11 or more, 0.12 or more, 0.13 or more, 0.14 or more, 0.15 or more, 0.16 or more, 0.17 or more, 0.18 or more, 0.19 or more, 0.20 or more, 0.21 or more, 0.22 or more, 0.23 or more, 0.24 or more, 0.25 or more, 0.26 or more, 0.27 or more, 0.28 or more, 0.29 or more, or 0.30 or more. In some embodiments, y is -0.3, optionally -0.2, optionally -0.1, optionally 0, optionally 0.1, optionally 0.2, or optionally 0.3.Optionally, y is -0.30 or more, -0.29 or more, -0.28 or more, -0.27 or more, -0.26 or more, -0.25 or more, -0.24 or more, -0.23 or more, -0.22 or more, -0.21 or more, -0.20 or more, -0.19 or more, -0.18 or more, -0.17 or more, -0.16 or more, -0.15 or more, -0.14 or more, -0.13 or more, -0.12 or more, -0.11 or more, -0.10 or more, -0.09 or more, -0.08 or more, -0.07 or more, -0.06 or more, -0.05 or more, -0.04 or more, -0.03 or more, 0.02 or more, -0.01 or more, 0.00 or more, 0.01 or more, 0.02 or more, 0.03 or more, 0.04 or more, 0.05 or more, 0.06 or more, 0.07 or more, 0.08 or more, 0.09 or more, 0.10 or more, 0.11 or more, 0.12 or more, 0.13 or more, 0.14 or more, 0.15 or more, 0.16 or more, 0.17 or more, 0.18 or more, 0.19 or more, 0.20 or more, 0.21 or more, 0.22 or more, 0.23 or more, 0.24 or more, 0.25 or more, 0.26 or more, 0.27 or more, 0.28 or more, 0.29 or more, or 0.3 or more.
[0032] It is understood that in some embodiments, Li need not be exclusively Li, but may be partially replaced with one or more elements selected from the group consisting of Mg, Sr, Na, K, and Ca. The one or more elements replacing Li are optionally present at 10 atomic % or less, optionally 5 atomic % or less, optionally 3 atomic % or less, optionally 2 atomic percent or less, these percentages being relative to the total Li in the material.
[0033] M provided in the first composition comprises Ni. The amount of Ni in the first composition is optionally 10 atomic percent to 100 atomic percent (at%) of the total M. Optionally, the Ni content of M is 75 at% or greater. Optionally, the Ni content of M is 80 at% or greater. Optionally, the Ni content of M is 85 at% or greater. Optionally, the Ni content of M is 90 at% or greater. Optionally, the Ni content of M is 95 at% or greater. Optionally, the Ni content of M is 75 at% or more, 76 at% or more, 77 at% or more, 78 at% or more, 79 at% or more, 80 at% or more, 81 at% or more, 82 at% or more, 83 at% or more, 84 at% or more, 85 at% or more, 86 at% or more, 87 at% or more, 88 at% or more, 89 at% or more, 90 at% or more, 91 at% or more, 92 at% or more, 93 at% or more, 94 at% or more, 95 at% or more, 96 at% or more, 97 at% or more, 98 at% or more, 99 at% or more, 99.5 at% or more, 99.9 at% or more, or 100 at% or more.
[0034] In some embodiments, M in the first composition is Ni alone or in combination with one or more additional elements. The additional element is optionally a metal. Optionally, the additional element may include or be one or more of Al, Mg, Co, Mn, Ca, Sr, Zn, Ti, Y, Cr, Mo, Fe, V, Si, Ga, or B. In certain embodiments, the additional element may include Mg, Co, Al, or a combination thereof. Optionally, the additional element may be Mg, Al, V, Ti, B, or Mn, or a combination thereof. Optionally, the additional element is selected from the group consisting of Mg, Al, V, Ti, B, or Mn. Optionally, the additional element is selected from the group consisting of Mg, Co, and Al. Optionally, the additional element is selected from the group consisting of Ca, Co, and Al. In some embodiments, the additional element is Mn or Mg, or both Mn and Mg. Optionally, the additional element is Mn, Co, Al, or any combination thereof. Optionally, the additional element includes Co and Mn. Optionally, the additional element is Co and Al. Optionally, the additional element is Co.
[0035] The additional element of the first composition may be present in an amount of about 1 to about 90 at%, specifically about 5 to about 80 at%, more specifically about 10 to about 70 at%, of M in the first composition. Optionally, the additional element may be present in an amount of about 1 to about 20 at%, specifically about 2 to about 18 at%, more specifically about 4 to about 16 at%, of M in the first composition. In some examples, M is about 75-100 at% Ni, 0-15 at% Co, 0-15 at% Mn, and 0-10 at% of the additional element.
[0036] Within a polycrystalline material, each crystallite may have any suitable shape, which may be the same or different within each grain. Furthermore, the shape of each crystallite may be the same or different within different grains. Due to the nature of the crystal, the crystallites may be faceted, the crystallites may have multiple flat surfaces, and the shape of the crystallites may approximate a geometric shape. In some embodiments, the crystallites may be fused with adjacent crystallites that have mismatched crystal faces. The crystallites may optionally be polyhedral. The crystallites may have a linear shape, and when viewed in cross section, some or all of the crystallites may be linear. The crystallites may be square, hexagonal, rectangular, triangular, or combinations thereof.
[0037] In certain embodiments, the secondary particles have grain boundaries enriched in Co and Al, and optionally the atomic percentages of Co and Al at the grain boundaries are greater than the atomic percentages of Co and Al in the crystallites averaged over the entirety. Referring to FIG. 1 as an exemplary illustration, the grain boundaries 20, 21 are between adjacent crystallites 10 and comprise a second composition. The second composition may be as described in U.S. Pat. Nos. 9,391,317 and 9,209,455, except that both Co and Al must be enriched at the grain boundaries independently relative to the concentrations of Co and Al in the crystallites, and that in some embodiments, synergistic effects in impedance reduction or cycle life improvement may be imparted due to the concentrations of Co and Al being within a particular concentration range. The second composition optionally has a layered α-NaFeO2 type structure, a cubic structure, or a combination thereof. As discussed above, the concentrations of Co and Al at the grain boundaries may be greater than the concentrations of Co and Al in the crystallites. Particular mention is made of an embodiment in which the grain boundaries have a layered α-NaFeO2 type structure. Particular mention is made of another embodiment in which the grain boundaries have a defective α-NaFeO2 type structure. Particular mention is made of another embodiment in which a portion of the grain boundaries has a cubic or spinel structure.
[0038] The second composition, which is present partially or entirely at the grain boundaries, is composition Li1+x FOR 2+ywhere -0.1≦x≦0.3 and -0.3≦y≦0.3. Optionally, the second composition and the first composition are identical except for the presence or higher concentration of Co and Al in the second composition compared to the first composition. In some embodiments of the second composition, x is -0.1, optionally 0, optionally 0.1, optionally 0.2, or optionally 0.3. Optionally, x is -0.10 or more, -0.09 or more, -0.08 or more, -0.07 or more, -0.06 or more, -0.05 or more, -0.04 or more, -0.03 or more, -0.02 or more, -0.01 or more, 0.00 or more, 0.01 or more, 0.02 or more, 0.03 or more, 0.04 or more, 0.05 or more, 0.06 or more, 0.07 or more, 0.08 or more, 0.0 9 or more, 0.10 or more, 0.11 or more, 0.12 or more, 0.13 or more, 0.14 or more, 0.15 or more, 0.16 or more, 0.17 or more, 0.18 or more, 0.19 or more, 0.20 or more, 0.21 or more, 0.22 or more, 0.23 or more, 0.24 or more, 0.25 or more, 0.26 or more, 0.27 or more, 0.28 or more, 0.29 or more, or 0.30 or more. In some embodiments, y is -0.3, optionally -0.2, optionally -0.1, optionally 0, optionally 0.1, optionally 0.2, or optionally 0.3.Optionally, y is -0.30 or more, -0.29 or more, -0.28 or more, -0.27 or more, -0.26 or more, -0.25 or more, -0.24 or more, -0.23 or more, -0.22 or more, -0.21 or more, -0.20 or more, -0.19 or more, -0.18 or more, -0.17 or more, -0.16 or more, -0.15 or more, -0.14 or more, -0.13 or more, -0.12 or more, -0.11 or more, -0.10 or more, -0.09 or more, -0.08 or more, -0.07 or more, -0.06 or more, -0.05 or more, -0.04 or more, -0.03 or more, -0 0.02 or more, -0.01 or more, 0.00 or more, 0.01 or more, 0.02 or more, 0.03 or more, 0.04 or more, 0.05 or more, 0.06 or more, 0.07 or more, 0.08 or more, 0.09 or more, 0.10 or more, 0.11 or more, 0.12 or more, 0.13 or more, 0.14 or more, 0.15 or more, 0.16 or more, 0.17 or more, 0.18 or more, 0.19 or more, 0.20 or more, 0.21 or more, 0.22 or more, 0.23 or more, 0.24 or more, 0.25 or more, 0.26 or more, 0.27 or more, 0.28 or more, 0.29 or more, or 0.3 or more.
[0039] M provided in the second composition includes Co and Al. When present, the amount of Ni is optionally between 0.01 atomic percent and 99 atomic percent (at%) of M. Optionally, M in the second composition does not include Ni. Optionally, the amount (i.e., relative concentration) of Ni in the second composition is less than the amount of Ni in the first composition in relative atomic percent (for each composition in which Ni is present). Optionally, the Ni content of M is 1 at% or less. Optionally, the Ni content of M is 5 at% or less. Optionally, the Ni content of M is 10 at% or less. Optionally, the Ni content of M is 20 at% or less. Optionally, the Ni content of M is 75 at% or less. Optionally, the Ni content of M is 80 at% or less. Optionally, the Ni content of M is 85 at% or less. Optionally, the Ni content of M is 90 at% or less. Optionally, the Ni content of M is 95 at% or less. Optionally, the Ni content of M is 75 at% or less, 76 at% or less, 77 at% or less, 78 at% or less, 79 at% or less, 80 at% or less, 81 at% or less, 82 at% or less, 83 at% or less, 84 at% or less, 85 at% or less, 86 at% or less, 87 at% or less, 88 at% or less, 89 at% or less, 90 at% or less, 91 at% or less, 92 at% or less, 93 at% or less, 94 at% or less, 95 at% or less, 96 at% or less, 97 at% or less, 98 at% or less, 99 at% or less, or 99.9 at% or less.
[0040] In the materials optionally provided herein, the nominal or total combined composition of the secondary particles (e.g., characterized by inductively coupled plasma (ICP)), optionally the first composition, or optionally the second composition, is defined by the formula LiMO, where M is Ni, and optionally the one or more additional metals in the second composition must include at least Co and Al. The mole fractions of Co and Al in the first composition, which defines the composition of the crystallites, if any, are lower than the separate or total mole fractions of Co and Al in the entire grain composition as determined by ICP. The separate or total mole fractions of Co and Al in the first composition may be zero. The separate or total mole fractions of Co and Al in the second composition, which defines the grain boundaries, are higher than the separate or total mole fractions of Co and Al in the entire grain as measured by ICP.
[0041] The second composition located within the grain boundaries comprises Co and Al, optionally with the proviso that the separate or combined concentrations of Co and Al in the grain boundaries are greater than the separate or combined concentrations of Co and Al in the crystallites, and optionally the concentration of Co in the grain boundaries is greater than the concentration of Co in the crystallites, and optionally the concentration of Al in the grain boundaries is greater than the concentration of Al in the crystallites. It has been found that a liquid solution containing 0 at% to 8 at% Co to be enriched, optionally 3 at% to 5 at% Co relative to the total transition metals of the first composition, can be supplemented with 0.01 at% to 10 at% Al, optionally up to 1.5 at% Al, using a process capable of enriching Co and Al in the grain boundaries, creating a material that exhibits a significant reduction in impedance increase during cycling, with the added Co and Al incorporated into the grain boundaries of the secondary particles.
[0042] Because the primary particle size distribution changes with changes in the overall composition and synthesis conditions, the volume fraction of the grain boundaries within a given secondary particle will change, so that the final concentrations of Co and Al in the second composition will always remain higher than those in the first composition, although they may vary between different secondary particles and even within individual secondary particles. Therefore, it is most useful to define the amounts of Co and Al added to the grain boundaries relative to the first composition.
[0043] The amount of Co and Al provided in the treatment solution is taken as the average amount of Co and Al added to the secondary particles and distributed at the grain boundaries throughout the secondary particles, and is shown relative to the M of the first composition. When producing the secondary particles described herein, it has been found that virtually all of the Co and Al in the treatment solution is attached to the particles before calcination. Therefore, the amount of Co and Al available for enriching the grain boundaries is the amount in the treatment solution. Thus, for example, when a treatment solution is described that is 1 at% Al and 2 at% Co, this at% is relative to the amount of M in the first composition before grain boundary enrichment. Therefore, the at% of Al and Co in the treatment solution used herein is always relative to the total M in the primary particles that are grain boundary enriched.
[0044] The amount of Al in the treatment solution is optionally between 0.01 at% and 10 at%, optionally 9 at% or less, optionally 8 at% or less, optionally 7 at% or less, optionally 6 at% or less, optionally 5 at% or less, optionally 4 at% or less, optionally 3 at% or less, optionally 2 at% or less, optionally 1 at% or less, optionally 0.1-1 at%, optionally 0.5-1 at%. Optionally, the amount of Al in the treatment solution is 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, or 1.5 atomic percent or less.
[0045] Optionally, the amount of Co in the treatment solution is greater than 3 at% up to 4 at% and the amount of Al is less than 1 at%, optionally between 0.1 and 1 at%, optionally between 0.1 at% and less than 1 at%. Optionally, the amount of Co in the treatment solution is between 0.5 at% and 4 at% and the amount of Al is between 0.01 at% and 10 at%.
[0046] In some embodiments, the amount of Co in the treatment solution is about 3 at%. At this Co concentration, the amount of Al is optionally less than 1 at%. To reduce impedance increase during cycling, an Al amount of about 0.3 at% to 0.7 at%, optionally about 0.5 at%, is optimal. Optionally, the Al is substantially uniformly distributed among the multiple secondary particles.
[0047] In some embodiments, the amount of Co in the treatment solution is about 3.5 at%. With this amount of Co, the amount of Al is optionally less than 1 at%. To reduce impedance increase during cycling, an amount of Al of about 0.3-0.7 at%, optionally about 0.5 at%, is optimal. Optionally, the Al is substantially uniformly distributed among the multiple secondary particles.
[0048] In some embodiments, the amount of Co in the treatment solution is about 4 at%. At this Co concentration, the amount of Al is optionally less than 1.5 at%. To reduce impedance increase during cycling, an Al amount of about 0.7-1.3 at%, optionally about 1.0 at%, is optimal. Optionally, the Al is substantially uniformly distributed among the multiple secondary particles.
[0049] In some embodiments, the amount of Co in the treatment solution is about 4.5 at%. At this Co concentration, the amount of Al is optionally less than 1 at%. To reduce impedance increase during cycling, an Al amount of about 0.3-0.7 at%, optionally about 0.5 at%, is optimal. Optionally, the Al is substantially uniformly distributed among the multiple secondary particles.
[0050] In some embodiments, the amount of Co in the treatment solution is about 3 at%. At this Co concentration, the amount of Al is optionally less than 1.5 at%. To reduce impedance increase during cycling, an amount of Al of about 0.5-1.3 at%, optionally about 1.0 at%, is optimal. Optionally, Al is substantially uniformly distributed among the multiple secondary particles.
[0051] In some embodiments, the amount of Co in the treatment solution is about 3 at% to about 4 at%. At this Co concentration, the amount of Al is optionally less than 1 at%. To reduce impedance increase during cycling, an Al amount of about 0.3 to 1.3 at%, optionally about 0.5 at% or about 1.0 at% is optimal. Optionally, Al is substantially uniformly distributed among the multiple secondary particles.
[0052] In some embodiments, the amount of Co in the treatment solution is about 3 at%. At this Co concentration, the amount of Al is optionally less than 1.5 at%. An Al amount of about 0.5 at% to 1.3 at% is optimal to reduce impedance increase during cycling. Optionally, Al is substantially uniformly distributed among the multiple secondary particles.
[0053] In some embodiments, the amount of Co in the treatment solution is about 4 at%. At this Co concentration, the amount of Al is optionally less than 1.0 at%. An Al amount of about 0.5 at% to 0.7 at% is optimal to reduce impedance increase during cycling. Optionally, Al is substantially uniformly distributed among the multiple secondary particles.
[0054] Thus, in some embodiments, the amount of Al that produces the most improved results moves from less than 1.3 at% to less than 0.7 at% as the amount of Co increases from 3 at% to 4 at%. Optionally, the Al is substantially uniformly distributed among the plurality of secondary particles.
[0055] Optionally, as shown by some embodiments of the secondary particles described herein, the amount of Al relative to the amount of Co in the second composition is 100 at% or less. This means that the amount of Al is optionally equal to or less than the amount of Co. Optionally, the amount of Al relative to Co is less than 90 at%, optionally less than 80 at%, optionally less than 70 at%, optionally less than 60 at%, optionally less than 50 at%, optionally less than 40 at%, optionally less than 30 at%, optionally less than 20 at%, optionally less than 10 at%, optionally less than 9 at%, optionally less than 8 at%, optionally less than 7 at%, optionally less than 6 at%, optionally less than 4 at%, optionally less than 3 at%, optionally less than 2 at%, and optionally less than 1 at%. It has been found that an amount of Co greater than the amount of Al allows for a synergistic relationship that unexpectedly reduces impedance increase compared to the same or higher concentration of Co alone.
[0056] Optionally, the Al present in the second composition or across some or all of the grain boundaries between multiple secondary particles is substantially uniform. For example, when Al is introduced by the methods provided herein for grain boundary enrichment of Al only, EDS of the powder by standard techniques results in the presence of Al-rich "hot spots," indicating uneven or inefficient grain boundary incorporation of Al resulting in separate phases of Al. However, the presence of Co and Al in the treatment solution at concentrations described herein results in a much more uniform distribution of Al, indicating a near or complete absence of hot spots observed by EDS. In some embodiments, the number and / or size of Al hot spots is reduced by 50% or more, optionally 60% or more, optionally 70% or more, and optionally 80% or more, compared to those resulting from grain boundary enrichment of Al without simultaneous enrichment of Co.
[0057] The uniformity of the aluminum can also be evaluated by comparing the EDS at two magnifications. Table 2 in Example 1 shows the aluminum concentration by EDS for a large area (approximately 150 μm×150 μm) as the first value in the table, followed by the second value which is the average EDS analysis of a much smaller area (approximately 1 μm×1 μm) centered on a grain with no obvious hot spots. With 4% cobalt in the treatment solution, these two values are close to each other. However, without cobalt, the small area that is not a hot spot has much less aluminum than the larger area, indicating that much more aluminum is concentrated in the hot spots rather than being distributed uniformly among multiple secondary particles.
[0058] In some embodiments, M in the second composition further comprises one or more elements substituting for Ni (substituting elements). The Ni substituting elements are optionally metals and are not Co or Al, since the presence of these elements results in an observed synergistic reduction in impedance increase. Optionally, the substituting elements can include or be one or more of Mg, Mn, Ca, Sr, Zn, Ti, Zr, Hf, Y, Cr, Mo, W, Fe, V, Nb, Ta, Si, Ga, or B. The substituting elements of the second composition can be present in an amount of about 1 to about 90 at%, specifically about 5 to about 80 at%, more specifically about 10 to about 70 at%, of the first composition. Optionally, the additional elements can be present in an amount of about 1 to about 20 at%, specifically about 2 to about 18 at%, more specifically about 4 to about 16 at%, of the first composition.
[0059] Optionally, the Li in the second composition need not be exclusively Li, but may be partially substituted with one or more Li-substituting elements selected from the group consisting of Mg, Sr, Na, K, and Ca. The one or more Li-substituting elements are optionally present at 10 at% or less, optionally 5 at% or less, optionally 3 at% or less, optionally 2 atomic percent or less, where the percentages are based on the total Li in the as-produced material.
[0060] The secondary particles provided herein can be produced by synthesizing a compact from at least two components, optionally in powder form. The at least two components may include micronized (or non-micronized) lithium hydroxide or its hydrate, a nickel-containing precursor hydroxide, and optionally one or more other elements, the precursor hydroxide being optionally obtained by a co-precipitation process. It is understood that the final overall composition (but not necessarily distribution) of elements in the final particles can be adjusted by increasing or decreasing the relative amounts of precursor materials in the formation of the compact. In some embodiments, the lithium hydroxide or its hydrate is micronized. The two or more powders forming the compact are mixed and shaken with a paint shaker to thoroughly mix the precursors. The compact is then calcined in a controlled air or pure oxygen atmosphere to a maximum temperature. The calcination is optionally performed according to a heating curve. The calcined product can then be processed to form a free-flowing powder.
[0061] In some embodiments, the precursor hydroxide may be a mixed metal hydroxide. In some embodiments, the mixed metal hydroxide may include a metal composition of Ni, Co, and Mg. Optionally, the mixed metal hydroxide includes, as metal components, 10-100 at% Ni, 0-15 at% Co, and 0-5 at% Mg. Optionally, the mixed metal hydroxide includes 10-100 at% Ni, 0-30 at% Co, and 0.1-80 at% Mn. Optionally, the mixed metal hydroxide includes 10-100 at% Ni, 0-30 at% Co, and 0-10 at% Al. Optionally, the metals of the mixed metal hydroxide are 92 at% Ni and 8 at% Co. Optionally, the metals of the mixed metal hydroxide are 90 at% Ni, 8 at% Co, and 2 at% Mg. Optionally, the metals of the mixed metal hydroxide are 89 at% Ni, 8 at% Co, and 3 at% Mg. Optionally, the metals of the mixed metal hydroxide are 91 at% Ni, 8 at% Co, and 1 at% Mg. Optionally, the metals of the mixed metal hydroxide are 100 at% Ni. For example, the precursor hydroxide may be produced by a precursor supplier, such as Hunan Brunp Recycling Technology Co. Ltd., using standard methods for producing nickel hydroxide-based materials.
[0062] The secondary particles can be formed by a multi-step process whereby particles of a first material are formed and calcined to form optionally defined grain boundaries in the primary particles having a low defect α-NaFeO2 structure. The particles are then subjected to a liquid process that applies Co and Al at desired concentration levels, followed by drying and then a second calcination, resulting in selective migration of surface Co and Al precipitate species to the grain boundaries, thereby forming secondary particles with higher concentrations of Co and Al at the grain boundaries than in the crystallites. According to the method of producing secondary particles having Ni, Co, and Mg bases provided herein as an example, the formation may include: mixing a lithium compound with one or more metal or semimetal hydroxide precursor compounds (e.g., mixed Ni, Co, and Mg, previously produced by a coprecipitation reaction, etc.) to form a mixture; heat treating the mixture at about 30 to about 200°C to form a dry mixture; heat treating the dried mixture at about 200 to about 500°C for about 0.1 to about 5 hours; and then heat treating at 600°C or higher and less than about 800°C for about 0.1 to about 10 hours to produce the secondary particles. The maximum temperature of the first calcination varies depending on the material used for the hydroxide precursor and is specific to that material. Optionally, in the first calcination, the maximum temperature may be 850°C or less, optionally 720°C or less, optionally 715°C or less, optionally 710°C or less, optionally 705°C or less, and optionally 700°C or less. Optionally, the maximum temperature of the first calcination may be about 680° C. or less. Optionally, the maximum temperature may be about 660° C. or less. Optionally, the maximum temperature may be about 640° C. or less. In yet another embodiment, the maximum temperature may be less than about 700° C., less than about 695° C., less than about 690° C., less than about 685° C., less than about 680° C., less than about 675° C., less than about 670° C., less than about 665° C., less than about 660° C., less than about 655° C., less than about 650° C., less than about 645° C., or less than about 640° C. The time at maximum temperature is optionally less than 10 hours.Optionally, the time at maximum temperature is 8 hours or less, optionally 7 hours or less, optionally 6 hours or less, optionally 5 hours or less, optionally 4 hours or less, optionally 3 hours or less, optionally 2 hours or less.
[0063] After calcination, subsequent processing may include grinding the calcined material with a mortar and pestle so that the resulting powder passes through a desired sieve, optionally a #35 sieve. The powder is then optionally ball milled in a 1 gallon jar containing a 2 cm drum YSZ media, optionally for 5 minutes, or for a time sufficient to allow the material to optionally pass through a #270 sieve.
[0064] The product of the first calcination or the milled product can then, optionally, be treated in such a way that enriched grain boundaries are obtained after the second calcination. The process of enriching the grain boundaries in the primary particles can be carried out by the methods or using the compositions shown in U.S. Pat. Nos. 9,391,317 and 9,209,455, except that the applied process uses a liquid solution containing a level of Co and a level of Al, optionally at levels that cause synergistic enrichment of Co and Al in the grain boundaries of the secondary particles. The grain boundary enrichment elements can be utilized by suspending the milled product, optionally at a temperature of about 60° C., in an aqueous slurry optionally containing Co, Al and a lithium compound, whereby Co and Al are present in the aqueous solution at the concentrations described herein. The slurry is then spray dried to form a free-flowing powder, which is then subjected to a second calcination, optionally with a heating curve following a two-step ramp / hold process. The first of the two ramp / hold temperature profiles may be from ambient temperature (about 25° C.) to 450° C., optionally at a rate of 5° C. per minute, with a hold at 450° C. for 1 hour. Then, the second ramp / hold may be from 450° C. to the maximum temperature at a rate of 2° C. per minute, with a hold at the maximum temperature for 2 hours. In some embodiments, the maximum temperature is less than about 725° C., optionally about 700° C. In other embodiments, the maximum temperature is about 725° C., optionally 750° C.
[0065] It has been found that by combining the initial calcination at the maximum temperature described above with the process of applying grain boundary enriched elements, followed by a second calcination also described above, the resulting particles can be used in a cathode to significantly improve and reduce impedance increase and / or capacity loss. Such a combination has been found to provide additional cycle life, reduce impedance increase, and significantly improve the electrochemical performance of the material. Thus, in some embodiments, a material having the composition Li 1+x MO 2+yIt is understood that the particles include a plurality of crystallites having a first composition comprising a polycrystalline layered structure lithiated metal oxide defined by: where -0.1≦x≦0.3 and -0.3≦y≦0.3. In some embodiments, x is -0.1, optionally 0, optionally 0.1, optionally 0.2, or optionally 0.3. Optionally, x is -0.10 or more, -0.09 or more, -0.08 or more, -0.07 or more, -0.06 or more, -0.05 or more, -0.04 or more, -0.03 or more, -0.02 or more, -0.01 or more, 0.00 or more, 0.01 or more, 0.02 or more, 0.03 or more, 0.04 or more, 0.05 or more, 0.06 or more, 0.07 or more, 0.08 or more, 0.0 9 or more, 0.10 or more, 0.11 or more, 0.12 or more, 0.13 or more, 0.14 or more, 0.15 or more, 0.16 or more, 0.17 or more, 0.18 or more, 0.19 or more, 0.20 or more, 0.21 or more, 0.22 or more, 0.23 or more, 0.24 or more, 0.25 or more, 0.26 or more, 0.27 or more, 0.28 or more, 0.29 or more, or 0.30 or more. In some embodiments, y is -0.3, optionally -0.2, optionally -0.1, optionally 0, optionally 0.1, optionally 0.2, or optionally 0.3.Optionally, y is -0.30 or more, -0.29 or more, -0.28 or more, -0.27 or more, -0.26 or more, -0.25 or more, -0.24 or more, -0.23 or more, -0.22 or more, -0.21 or more, -0.20 or more, -0.19 or more, -0.18 or more, -0.17 or more, -0.16 or more, -0.15 or more, -0.14 or more, -0.13 or more, -0.12 or more, -0.11 or more, -0.10 or more, -0.09 or more, -0.08 or more, -0.07 or more, -0.06 or more, -0.05 or more, -0.04 or more, -0.03 or more, 0.02 or more, -0.01 or more, 0.00 or more, 0.01 or more, 0.02 or more, 0.03 or more, 0.04 or more, 0.05 or more, 0.06 or more, 0.07 or more, 0.08 or more, 0.09 or more, 0.10 or more, 0.11 or more, 0.12 or more, 0.13 or more, 0.14 or more, 0.15 or more, 0.16 or more, 0.17 or more, 0.18 or more, 0.19 or more, 0.20 or more, 0.21 or more, 0.22 or more, 0.23 or more, 0.24 or more, 0.25 or more, 0.26 or more, 0.27 or more, 0.28 or more, 0.29 or more, or 0.3 or more. The crystallite has an amount of Ni between 10 atomic percent and 100 atomic percent (at%) of the M element. Optionally, the Ni component of M is 75 at% or more. Optionally, the Ni content of M is 80 at% or more. Optionally, the Ni content of M is 85 at% or more. Optionally, the Ni content of M is 90 at% or more. Optionally, the Ni content of M is 95 at% or more. Optionally, the Ni content of M is 75 at% or more, 76 at% or more, 77 at% or more, 78 at% or more, 79 at% or more, 80 at% or more, 81 at% or more, 82 at% or more, 83 at% or more, 84 at% or more, 85 at% or more, 86 at% or more, 87 at% or more, 88 at% or more, 89 at% or more, 90 at% or more, 91 at% or more, 92 at% or more, 93 at% or more, 94 at% or more, 95 at% or more, 96 at% or more, 98 at% or more, 99 at% or more, or 100 at%. The M content may include one or more additional elements. The additional element is optionally a metal.Optionally, the additional element can include or be one or more of Al, Mg, Co, Mn, Ca, Sr, Zn, Ti, Y, Cr, Mo, Fe, V, Si, Ga, or B. In certain embodiments, the additional element can include Mg, Co, Al, or a combination thereof. Optionally, the additional element can be Mg, Al, V, Ti, B, or Mn, or a combination thereof. Optionally, the additional element consists of Mg, Al, V, Ti, B, or Mn. In some embodiments, the additional element is Mn or Mg, or both Mn and Mg. The additional element of the first composition can be present in an amount of about 1 to about 90 at% of the first composition, specifically about 5 to about 80 at%, more specifically about 10 to about 70 at%. Optionally, the additional element may be present in an amount of about 1 to about 20 at%, specifically about 2 to about 18 at%, more specifically about 4 to about 16 at% of the first composition. In some examples, M is about 75 to 100 at% Ni, 0 to 15 at% Co, 0 to 15 at% Mn, and 0 to 10 at% additional element. The resulting secondary particles have grain boundaries, whereby the amount of Co and the amount of Al are higher than in the crystallites.
[0066] The resulting particles optionally exhibit reduced impedance increase compared to particles having only Co enriched grain boundaries, optionally at levels of Co that were believed to be insufficient to significantly improve the cycling characteristics of particles not enriched in Co at the grain boundaries. When the resulting secondary particles are the active material of a Li-ion cell cathode, cells cycled between 4.2V and 2.7V at 45°C optionally exhibit less than 50% impedance increase in the fully charged (4.2V) state for more than 50 cycles, optionally more than 60 cycles, optionally more than 70 cycles, optionally more than 80 cycles, optionally more than 90 cycles, optionally more than 100 cycles, optionally more than 110 cycles, optionally more than 120 cycles, optionally more than 130 cycles, optionally more than 140 cycles, optionally more than 150 cycles, and optionally more than 200 cycles.
[0067] In another aspect, cells cycled between 4.2V and 2.7V at 45°C exhibit less than 100% impedance increase in the fully charged (4.2V) state for more than 100 cycles, optionally more than 110 cycles, optionally more than 120 cycles, optionally more than 130 cycles, optionally more than 140 cycles, optionally more than 150 cycles, optionally more than 160 cycles, optionally more than 170 cycles, optionally more than 180 cycles, optionally more than 190 cycles, optionally more than 200 cycles, optionally more than 210 cycles, and optionally more than 220 cycles.
[0068] In another aspect, cells cycled between 4.2V and 2.7V at 45°C optionally exhibit an impedance increase at 50% state of charge (SOC) of less than 50% over more than 200 cycles, optionally less than 40% over more than 200 cycles, and optionally less than 30% over more than 200 cycles.
[0069] The electrochemical cells provided herein optionally use as electrochemically active material particles the particles provided herein having an initial discharge capacity of 180 mAh / g or greater, optionally 185 mAh / g, optionally 190 mAh / g, optionally 195 mAh / g, optionally 200 mAh / g, and optionally 210 mAh / g.
[0070] Disclosed is a particle comprising crystallites 10 comprising a first composition and grain boundaries 20, 21 comprising a second composition, as shown in FIG. 1, where the concentration of Al at the grain boundaries is greater than the concentration of Al in the crystallites, and the concentration of cobalt at the grain boundaries is greater than the concentration of cobalt in the crystallites. The particle comprises a plurality of crystallites, which are referred to as secondary particles. Optionally, an outer layer, such as a passivation or protective layer, shown at 30 in FIG. 1, may be deposited on the outer surface of the particle. The outer layer may completely or partially cover the secondary particles. The layer may be amorphous or crystalline. The layer may comprise an oxide, phosphate, pyrophosphate, fluorophosphate, carbonate, fluoride, oxyfluoride, or combinations thereof, of an element such as Al, Ti, B, Li, or Si, or combinations thereof. In some embodiments, the outer layer comprises a borate, an aluminate, a silicate, a fluoroaluminate, or combinations thereof. Optionally, the outer layer comprises a carbonate. Optionally, the outer layer comprises ZrO2, Al2O3, TiO2, AlPO4, AlF3, B2O3, SiO2, Li2O, Li2CO3, or a combination thereof. Optionally, the outer layer comprises or is AlPO4 or Li2CO3. This layer can be deposited and disposed by any process or technique that does not adversely affect the desired properties of the particle. Exemplary methods include, for example, spray coating and dip coating.
[0071] Also provided is an electrode comprising the secondary particles described herein as a component of an electrochemically active material or as the only electrochemically active material. The secondary particles provided herein are optionally included as an active component of a cathode. The cathode optionally comprises the secondary particles disclosed above as an active material, and may further comprise a conductive agent and / or a binder. The conductive agent may comprise any conductive agent that provides suitable properties and may be amorphous, crystalline, or a combination thereof. The conductive agent may comprise carbon black, such as acetylene black or lamp black, mesocarbon, graphite, graphene, carbon fibers, carbon nanotubes, such as single-walled or multi-walled carbon nanotubes, or a combination thereof. The binder can include any binder that imparts suitable properties, and can include, for example, polyvinylidene fluoride, copolymers of polyvinylidene fluoride and hexafluoropropylene, poly(vinyl acetate), poly(vinyl butyral-co-vinyl alcohol-co-vinyl acetate), poly(methyl methacrylate-co-ethyl acrylate), polyacrylonitrile, polyvinyl chloride-co-vinyl acetate, polyvinyl alcohol, poly(1-vinylpyrrolidone-co-vinyl acetate), cellulose acetate, polyvinylpyrrolidone, polyacrylates, polymethacrylates, polyolefins, polyurethanes, polyvinyl ethers, acrylonitrile-butadiene rubber, styrene-butadiene rubber, acrylonitrile-butadiene-styrene, sulfonated styrene / ethylene-butylene / styrene triblock polymers, polyethylene oxide, or combinations thereof.
[0072] The cathode can be made by combining the particles, conductive agent, and binder described herein in suitable ratios, for example, about 80 to about 98 weight percent of the particles, about 1 to about 20 weight percent of the conductive agent, and about 1 to about 10 weight percent of the binder, based on the total weight of the particles, conductive agent, and binder combined. The particles, conductive agent, and binder can be suspended in a suitable solvent, such as N-methylpyrrolidinone, placed on a suitable substrate, such as aluminum foil, and dried in air. It should be noted that the substrate and solvent are shown for illustrative purposes only. Other suitable substrates and solvents can be used or combined to form the cathode.
[0073] The cathodes provided herein exhibit a significantly reduced impedance increase when cycled in a 2025 coin cell with an MCMB 10-28 graphite anode, a polyolefin separator, and an electrolyte of 1M LiPF6 in 1 / 1 / 1 (by volume) EC / DMC / EMC with 1 wt% VC, optionally compared to materials enriched solely in Co or without grain boundary enrichment. One measure of impedance increase can be obtained by high rate cycling of the cell with 1C / 1C charge / discharge cycles interspersed in a cycling regime of 20 cycles apart. The voltage is held after a 1C charge to 4.2V during which the cell voltage is maintained at 4.2V until the current decays to a C / 10 rate, after which the cell is rested at open circuit for 5 minutes. Then, when the fully charged cell is discharged, the voltage drop during the first 10 seconds of discharge and the discharge rate of 1C are fitted to Ohm's law (V=IR) to calculate the DCR (direct current resistance) measurement of the cell impedance. The impedance measurement plotted against the number of cycles results in a curve with a defined slope. When the active particle material has grain boundaries enriched in Co and Al as described herein, the impedance slope is smaller compared to particles that do not have such enriched grain boundaries or compared to particles that have grain boundaries enriched only in Co. In some embodiments, the cell impedance increases by 25% or less in the first 50 cycles, optionally 50% or less in the first 100 cycles, optionally 63% or less in the first 125 cycles, and optionally 75% or less in the first 150 cycles. Optionally, the impedance increases by 25% or less in 50 cycles, optionally 50% or less in 100 cycles, optionally 63% or less in 125 cycles, and optionally 75% or less in the first 150 cycles.
[0074] Also disclosed is a battery comprising the cathode. The battery may be, for example, a lithium ion battery, a lithium polymer battery, or a lithium battery. The battery may comprise a cathode, an anode, and a separator sandwiched between the cathode and the anode. The separator may be a microporous membrane, which may comprise a porous film comprising polypropylene, polyethylene, or a combination thereof, or may be a woven or non-woven material, such as a glass fiber mat. The anode may comprise a coating on a current collector. The coating may comprise, for example, a suitable carbon, such as graphite, coke, hard carbon, or mesocarbon, such as mesocarbon microbeads. The current collector may be, for example, a copper foil.
[0075] The battery also includes an electrolyte that may be in contact with the positive electrode (cathode), the negative electrode (anode), and the separator. The electrolyte may include an organic solvent and a lithium salt. The organic solvent may be a linear or cyclic carbonate. Representative organic solvents include ethylene carbonate, propylene carbonate, butylene carbonate, trifluoropropylene carbonate, gamma-butyrolactone, sulfolane, 1,2-dimethoxyethane, 1,2-diethoxyethane, tetrahydrofuran, 3-methyl-1,3-dioxolane, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, dipropyl carbonate, methyl propyl carbonate, propane sultone, or combinations thereof. In another embodiment, the electrolyte is a polymer electrolyte.
[0076] Representative lithium salts useful in the electrolyte include, but are not limited to, LiPF6, LiBF4, LiAsF6, LiClO4, LiCF3SO3, Li(CF3SO2)2N, LiN(SO2C2F5)2, LiSbF6, LiC(CF3SO2)3, LiC4F9SO3, and LiAlCl4. The lithium salt can be dissolved in an organic solvent. Combinations comprising at least one of the foregoing can be used. The concentration of the lithium salt can be 0.1 to 2.0 M in the electrolyte.
[0077] The electrolyte may be a solid ceramic electrolyte.
[0078] The battery may have any suitable configuration or shape and may be cylindrical or prismatic.
[0079] Various aspects of the present disclosure will now be illustrated by the following non-limiting examples. The examples are intended to be illustrative and not limiting to the practice of the invention. It will be understood that changes and modifications can be made without departing from the spirit and scope of the invention.
[0080] Working Example Example 1: Polycrystalline 2D α-NaFeO2-type layered structure particles with grain boundaries enriched with Al and Co.
[0081] Electrochemically active polycrystalline 2D α-NaFeO2-type layered structure particles with and without different types of grain boundary enrichment were fabricated, each containing nickel rich in the cathode material.
[0082] Li 1.03 Mg 0.01 Ni 0.92 Co 0.08 The material, with the composition O2, was mixed in a 1-liter jar with 252.1 g Li(OH)2 (LiOH*H2O, dehydrated and micronized, from FMC) and 961.6 g Ni 0.91 Co 0.08 Mg 0.01 (OH)2 (custom made) were dry mixed. The compounds were mixed by shaking the jar in a paint shaker.
[0083] The mixed compounds were placed in an alumina crucible and sintered. Sintering was performed by heating at a rate of about 5°C per minute to about 450°C and holding at about 450°C for about 2 hours. The temperature was then increased at about 2°C per minute to about 700°C and held for about 6 hours. The samples were then allowed to cool naturally to room temperature. The cooled samples were crushed for about 5 minutes to break up the agglomerates and extract the Li 1.03 Mg 0.01Ni 0.92 Co 0.08 The material was analyzed by XRD and showed a structure of the α-NaFeO2 type.
[0084] Using the above base material, samples of secondary particles with grain boundary enrichment of Co and Al were prepared in 100 g each. Nitrates of Li, Co, and Al were dissolved in 100 g of H2O heated to 60 °C. The amounts of Al and Co added were: Li 1.03 Mg 0.01 Ni 0.92 Co 0.08 The amount of LiNO3 added was such that the final Li to transition metals + Al ratio was 1.01.
[0085] 100g of Li produced above 1.03 Mg 0.01 Ni 0.92 Co 0.08 O2 was added to it and the resulting slurry was stirred for 30-120 minutes. The slurry was then spray dried to obtain powders. The resulting powders were placed in an alumina crucible and heated to about 450°C at a rate of about 5°C per minute and held at about 450°C for about 1 hour. The temperature was then increased to about 700°C at about 2°C per minute and held for about 2 hours. Each material was then allowed to cool naturally to 100°C. The calcined materials were ground separately, first in a mortar and pestle and then in a ball mill.
[0086] Overall, based on their synthesis recipes, four materials with or without grain boundary enrichment with Al and / or Co with the final bulk compositions shown in Table 1 were produced using the procedures described above.
[0087] [Table 1]
[0088] The resulting materials and controls were blended with PVDF binder and conductive carbon, respectively, in a slurry in NMP solvent and coated onto aluminum foil current collectors. Similar coatings of selected materials were also fabricated on Cu foils so that Al distribution could be analyzed by FIB-STEM-EDS without the risk of measuring the Al originating from the foil. Cathode electrodes were then punched out of the foils and combined with MCMB 10-28 graphite anodes, porous polypropylene separators, and carbonate-based electrolytes in Li-ion "full" coin cell formats for electrochemical cycle life testing. Cathode electrodes were also combined with lithium metal anodes, porous polypropylene separators, and carbonate-based electrolytes in "half" coin cell formats for electrochemical discharge capacity testing.
[0089] The full cells were cycled through a series of charge and rapid discharge cycles at 45° C. The low-rate discharge capacity and impedance values were measured every 20 charge / discharge cycles. Some materials were further analyzed by EDS and cross-sectional TEM / EDX before being used for cathode formation.
[0090] Figures 2 and 3 show the capacity fade and associated impedance increase for full cells cycled at 45°C. Figure 2 shows that the "no grain boundary enrichment process" (no slurry, spray drying, or second calcination) and "no grain boundary enrichment elements" (no Co or Al solutes in the aqueous slurry, spray drying, and second calcination) samples faded in capacity at roughly the same high rate. The "no grain boundary enrichment elements" material underwent an aqueous slurry and subsequent calcination process, but only water was used, which does not contain the grain boundary enrichment elements. Figure 3 shows that the two materials also had similar impedance increase rates, indicating that the water immersion, spray drying, and second calcination processes did not have a significant impact. The aluminum-only sample showed a slight improvement over the baseline with no grain boundary enrichment elements, but the largest improvement was observed with the cobalt-only grain boundary enrichment, with a 10% fade over 300 cycles.
[0091] Sample grain boundaries (GBs) enriched with both cobalt and aluminum samples did not show improved capacity fade over cobalt alone. However, as shown in Figure 3, this resulted in a significantly smaller impedance increase, with an impedance increase of approximately 50% at full charge after 100 cycles and an impedance increase of approximately 115% after 200 cycles. Materials GB enriched with both Co and Al showed a 30% lower impedance increase than materials GB enriched with Co alone, and did so without the use of additional Co.
[0092] As shown by EDS mapping of the calcined material and shown in Figure 4, cobalt significantly improves aluminum incorporation, as a separate phase of lithiated alumina is observed in the absence of Co in the treatment solution. The image below the EDS elemental map of Al (bright spots) shows that the material with only Al in the treatment solution had stronger and more Al "hot spots" than the material with Co in the treatment solution along with Al. This indicates that the addition of Co to the process formulation distributed Al more evenly among multiple secondary particles, suggesting that Co incorporated much more Al into the particles when calcined.
[0093] The more uniform distribution and incorporation of Al among the secondary particles when combined with Co in the treatment solution was also demonstrated by comparing the quantitative EDS results for Al analysis of particles over a large area (approximately 150 μm × 150 μm) to that obtained by averaging three spot (approximately 1 μm × 1 μm) analyses obtained in non-hot spot locations. Table 2 shows these comparisons for cathode particles combined with Al only and cathode particles combined with Al and Co, and shows that the localized non-hot spot analysis of the Co and Al combined gave Al content results similar to those obtained over a larger area, suggesting that the Al was substantially uniformly distributed among the secondary particles. In contrast, the material combined with Al only had much lower non-hot spot Al analysis results than the larger area, suggesting that much of the Al was concentrated in the hot spot particles rather than uniformly distributed among the secondary particles.
[0094] [Table 2]
[0095] Quantitative STEM / EDS spot analysis of thin lamellae of the two materials confirmed that the inclusion of Co in the Al-containing process formulations promoted the incorporation of Al into the grain boundaries during subsequent calcination. Secondary particles of each material coated on Cu foil as described above were cut by focused ion beam (FIB) milling to obtain thin lamellae with a thickness of about 100 nm. Figure 5 shows a scanning transmission electron micrograph (STEM) image of a small area containing multiple crystallites from a particle produced by the grain boundary enrichment process in which both 1.9 at% Al and 4 at% Co were formulated in the treatment solution, indicating the locations where three EDS spot analyses were performed. Locations 1 and 3 are inside adjacent crystallites, while location 2 is at the grain boundary between them. Figure 6 shows the EDS spectra collected at the three locations marked in Figure 5. Spectrum 2 at the grain boundary shows a clear peak for Al at about 1.5 keV, while spectra 1 and 3 inside the crystallites do not. Spectrum 2 at the grain boundary also shows a higher ratio of Co to Ni than is seen in the crystallite interiors in spectra 1 and 3, as shown by comparing the 6.9 keV Co peak with the 8.3 keV Ni peak in each spectrum. Quantitative results obtained by integrating the spectra in Figure 6 are given in Table 3 and show that both Al and Co are enriched at the grain boundary locations in spectrum 2.
[0096] [Table 3]
[0097] The same type of STEM-EDS analysis was performed on particles produced by the grain boundary enrichment process with 1.9 at% Al in the treatment solution in the absence of Co. The STEM images and EDS point analysis locations are shown in Figure 7. The location of spectrum 1 is at the grain boundary and the location of spectrum 2 is inside the crystallite. Figure 8 shows the EDS spectra collected at the two locations marked in Figure 7. Neither spectrum shows the presence of Al and there is little difference between these Co peaks. The quantitative results obtained by integrating the spectra in Figure 8 are shown in Table 4. This shows that the composition of the grain boundary and the bulk crystallites is identical, suggesting little or no Al incorporation or grain boundary enrichment in the secondary particles.
[0098] [Table 4]
[0099] STEM-EDS point analyses of the type described above were performed at a total of 11 grain boundary and 10 intra-crystallite locations for the 1.9 at% Al, 4 at% Co grain boundary enriched material, and 16 grain boundary and 7 intra-crystallite locations for the material enriched with 1.9 at% Al only. Table 5 shows the average results of these analyses compared to the bulk formulation of the material, and indicates that liquid processing using only Al followed by calcination results in little or no grain boundary Al enrichment (measurable amounts of Al detected at 3 out of 16 locations), while processing with both Al and Co followed by calcination results in significant enrichment of both elements at the grain boundaries.
[0100] [Table 5]
[0101] Example 2: Grain boundary enrichment in both Al and Co by a non-aqueous grain boundary enrichment process.
[0102] Electrochemically active polycrystalline 2D α-NaFeO2-type layered structure particles with different types of grain boundary enrichment in the cathode materials and rich in nickel were fabricated by a non-aqueous grain boundary enrichment process. 1.03 Mg 0.01 Ni 0.92 Co 0.08 A material with a composition of O2 was produced by the method of Example 1. 30 g of this material was then dispersed in 40 ml of methanol containing 1.9 at% Al as dissolved nitrate, with or without 4 at% Co nitrate, along with sufficient LiNO3 to give a final transition metals+Al ratio of Li to 1.01. The resulting slurry was dried on a rotary evaporator, after which the recovered material underwent the same calcination procedure as applied to the spray-dried material of Example 1. FIG. 9 shows the Al EDS map of the calcined material, showing that, as seen with the aqueous process material of Example 1, the material formulated with only Al had stronger and more Al "hot spots" than the material formulated with Co along with Al. This result indicates that the role of solution processing with Co in promoting more uniform incorporation of Al by secondary particles is not an artifact of the aqueous process, and that non-aqueous deposition of grain boundary enriched elements by solvent evaporation gives the same results as aqueous deposition by acid-base precipitation.
[0103] Example 3: Synergistic benefits obtained by grain boundary enrichment with both Al and Co.
[0104] The electrochemically active polycrystalline 2D α-NaFeO2-type layered structure particles with different types of grain boundary enrichment in the cathode material and rich in nickel were prepared by the method of Example 1, using Li 1.03 Mg 0.01 Ni 0.92 Co 0.08 The Al and Co process formulations used to produce these materials are shown in the matrix in Table 6.
[0105] [Table 6]
[0106] Lithium ion coin cells were assembled using the materials enriched as per Table 6 and cycled according to the method of Example 1. Figure 10 shows the cycle capacity fade for cells using 0 at% Al grain boundary enriched material and 0.5 at% Al grain boundary enriched material and their dependence on the incorporated Co content. The capacity of the various materials decreases with increasing Co in the formulation, but the rate of capacity fade is not significantly different, ranging from 4% to 6% over 200 cycles, with little effect seen with or without 0.5 at% Al in the formulation. However, Figure 11 shows that increasing the Co level in the formulation reduces the impedance increase, reducing the impedance increase at 4.2 V at 200 cycles from 250% to 130% as the formulated Co level is increased from 3 at% to 4 at%, and that the inclusion of an additional 0.5 at% Al in the solution process formulation significantly reduces the impedance increase at all levels of Co in the formulation, reducing the impedance increase at 200 cycles from 150% to 90% as the Co level in the solution process formulation is increased from 3 at% to 4 at%. Figure 12 further shows that a synergistic benefit is observed with the inclusion of Al in the solution process formulation, reducing the impedance more than obtained by further increasing the Co concentration alone.
[0107] Figure 13 shows the cycling capacity drop (left) and impedance increase (right) for cells with grain boundary enriched cathode material from a 3 at% Co solution process formulation with various Al levels. The figure shows that increasing the formulated Al level reduces the capacity of the cathode material with little effect on the capacity fade (all cells drop in the range of 6%-8% over 200 cycles), but increasing the formulated Al level from 0 at% to 1 at% reduces the impedance increase at 4.2 V at 200 cycles from 200% to 120%, while further increasing the Al level slightly increases the impedance increase. The impedance increase plotted in Figure 13 is summarized in Figure 14. It shows that when 3 at% Co is included in the process solution along with Al, the smallest impedance increase is obtained when the process solution has an at% ratio of formulated Al / Co of about 0.3-0.4.
[0108] Example 4: Grain boundary enrichment of Al and Co in NCA materials.
[0109] Two NCA materials of similar bulk composition were produced, one with grain boundary enrichment of Co and Al and the other without. In each case, the base material was produced by blending hydroxide precursors together and firing in an oxygen atmosphere until the final lithiated oxide was formed and sintered.
[0110] Material 1: First composition LiNi 0.93 Co 0.04 Al 0.03 An NCA-based material having O2 and enriched at the grain boundaries with an additional 4 at% Co and 0.6 at% Al relative to the total M in the first composition.
[0111] For this process, a precursor transition metal hydroxide was used, which contained 4 at% Co and 3 at% Al among the transition metals, with the balance being Ni. Micronized LiOH powder was produced by placing 51 g of LiOH in a plastic jar containing 500 g of Y-stabilized zirconia 1 / 4 inch balls and shaking on a paint shaker for 45 minutes. This micronized powder was then transferred to another plastic jar containing 190.15 g of the transition metal hydroxide precursor, and the two powders were blended by shaking the jar on a paint shaker for an additional 10 minutes. After blending, approximately 240 g of the blended powder was split into two crucibles and fired in an oxygen atmosphere by first ramping at 5°C / min to 450°C and soaking at that temperature for 2 hours, then ramping at 2°C / min to 680°C and soaking for 6 hours. After this heating schedule was completed, the furnace was allowed to cool to 130°C and the powder was removed and placed in a ball mill. The ball mill contained 1 / 2 inch drum media and was used to grind the powder for 2 minutes. The powder was then sieved through a 270 mesh sieve. The material was analyzed by XRD, which showed an α-NaFeO2 type structure.
[0112] The powder was then coated with Co and Al by making a solution of 80 g water, 9.5 g cobalt nitrate (4 at% Co relative to total M in the LiMO2-based composition), 1.9 g aluminum nitrate (0.6 at% Al relative to total M in the LiMO2-based composition), and 2.7 g lithium nitrate and heating to 60°C. To this was added 80 g of the previously prepared powder. The slurry was stirred for 25 minutes and then spray dried to remove water from the slurry and prepare a dry powder. The powder was then calcined in an air atmosphere by first heating at 5°C / min to 450°C and soaking for 1 hour, then heating at 2°C / min to 700°C and soaking for 2 hours. The furnace was then allowed to cool to 130°C and the powder was removed from the furnace and sieved through a 270 mesh sieve. Figure 15 shows a STEM microscopy image of a thin-sectioned secondary particle of the material thus prepared and coated onto a Cu foil as described in Example 1. Figure 15 also shows the Al / Ni and Co / N atomic ratio results for three EDS point analyses of the internal grain boundaries (GBs) and the bulk regions of adjacent primary particles, indicating that both Co and Al are enriched at the grain boundaries.
[0113] Material 2: homogeneous first composition LiNi 0.89 Co 0.08 Al 0.03 Comparison of NCA-based materials with O2 For this process, a precursor transition metal hydroxide was used, which contained 8 at% Co and 3 at% Al, with the balance being Ni. Micronized LiOH powder was produced by placing 25.5 g of LiOH in a plastic jar containing 500 g of Y-stabilized zirconia 1 / 4 inch spheres and shaking on a paint shaker for 45 minutes. This micronized powder was then transferred to another plastic jar containing 95.1 g of transition metal hydroxide and the two powders were blended by shaking on a paint shaker for an additional 10 minutes. After blending, approximately 120 g of the powder was placed in a crucible and fired in an oxygen atmosphere by first ramping at 5°C / min to 450°C and soaking at that temperature for 2 hours, then ramping at 2°C / min to 680°C and soaking for 6 hours. The furnace was then allowed to cool to 130°C and the powder was removed and placed in a ball mill. The ball mill contained 1 / 2 inch drum media, which was used to grind the powder for 2 minutes. The powder was then sieved through a 270 mesh sieve. The material was analyzed by XRD and showed an α-NaFeO2 type structure.
[0114] The cathode materials 1 and 2 above were assembled into coin cells as described in Example 1. The cells were cycled 1C / 1C at 45°C and the 10 s discharge DCR was measured at 100% state of charge (SOC) every cycle and at 50% SOC every 20 cycles. The capacity fade and impedance increase results of two Li-ion coin cells fabricated with each material are shown in Figures 16 and 17, respectively. The overall compositions of the two materials were nearly equivalent, but the grain boundary enriched material #1 contained Co concentrated between the bulk crystallites at the grain boundaries, and material #2 contained a similar overall amount of Co distributed uniformly throughout the secondary particles. Material #1 had only a slightly higher overall Al content than material #2, but all of the excess Al (about 16% more Al than material #2) was concentrated in the grain boundaries. Both the capacity fade and impedance increase were significantly improved for the GBE material when compared to the materials of uniform composition. Figure 16 shows that grain-enriched material #1 had only an 8% capacity drop over 200 cycles compared to a greater than 30% drop for material #2, in addition to having slightly more capacity (~1%) than homogeneous material #2. Figure 17 shows that the cell with grain-enriched material #1 had a 100% impedance increase at full SOC (4.2V) after 200 cycles and a 30% impedance increase at 50% SOC, while the cell with material #2 had a greater than 800% impedance increase at full SOC and a greater than 200% impedance increase at 50% SOC after 200 cycles.
[0115] Example 5: Al and Co grain boundary enrichment in NCM materials.
[0116] First composition LiNi 0.8 Co 0.1 Mn 0.1NCM-based material with O2 (NCM811) was produced from a co-precipitated precursor transition metal hydroxide containing 10 at% Co, 10 at% Mn, and the balance Ni. Finely divided LiOH powder was produced by placing 87.7 g of LiOH in a plastic jar containing 500 g of Y-stabilized zirconia 1 / 4 inch spheres and shaking on a paint shaker for 45 minutes. This finely divided powder was then transferred to another plastic jar containing 335.7 g of the precursor transition metal hydroxide and blended by shaking the two on a paint shaker for an additional 10 minutes. After blending, approximately 440 g of powder was divided into three crucibles and fired in an oxygen atmosphere by first ramping at 5°C / min to 450°C and soaking at that temperature for 2 hours, then ramping at 2°C / min to 770°C and soaking at 770°C for 10 hours. The furnace was then allowed to cool to 130°C and the powder was removed and placed in a ball mill. The ball mill contained 3 / 4 inch drum media and was used to grind the powder for 2 minutes. The powder was then sieved through a 270 mesh sieve.
[0117] The powder was then divided into base (no further treatment) or grain boundary enriched with Co and Al by preparing a solution of 200 g water, 11.9 g cobalt nitrate (2 at% Co relative to the base composition), 3.1 g aluminum nitrate (0.4 at% Al) and 3.4 g lithium nitrate and then heating to 60°C. To this was added 200 g of the previously prepared lithiated precursor powder. The slurry was stirred for 10 minutes and then spray dried to remove the water from the slurry and prepare a dry powder. The powder was then calcined in an air atmosphere by first ramping at 5°C / min to 450°C and soaking at that temperature for 1 hour, then ramping at 2°C / min to 770°C and soaking for 0.25 hours. The furnace was then allowed to cool to 130°C and the powder was removed from the furnace and sieved through a 270 mesh sieve. The overall composition of the synthesized cathode powder was LiNi 0.079 Co 0.11 Mn 0.09 Al 0.006 It was O2.
[0118] The base material and grain boundary enriched NCM material were then assembled into Li coin cells and cycled at 45° C. by the methods described in Examples 1 and 4. The capacity fade and impedance increase results of two Li-ion coin cells fabricated with each material are shown in FIG. 18 and FIG. 19, respectively. Both materials showed good cycling stability (FIG. 18), with the grain boundary enriched material fading slightly less (about 4% at 200 cycles versus about 5% for the base material) and a slightly lower initial capacity. Nevertheless, the grain boundary enriched material showed a much lower impedance increase than the homogeneous base material of similar composition (FIG. 19), with a 45% impedance increase at 100% SOC and a 38% impedance increase at 50% SOC after 200 cycles compared to a 225% impedance increase at 100% SOC and a 70% impedance increase at 50% SOC for the base material after 200 cycles. These results indicate that grain boundary enrichment with Al and Co at relatively low levels is beneficial for NCM.
[0119] Various modifications will be apparent to those skilled in the art from the above description, in addition to those shown and described herein, and such modifications are intended to be included within the scope of the present disclosure.
[0120] Unless otherwise specified, it is understood that all reagents are available from suppliers known in the art.
[0121] The patents, publications, and applications mentioned in this specification are indicative of the level of skill of those skilled in the art to which the disclosure pertains, and are herein incorporated by reference to the same extent as if each individual patent, publication, or application was specifically and individually indicated to be incorporated by reference.
[0122] The foregoing description illustrates certain embodiments of the present invention but is not meant to limit its practice.
Claims
1. a plurality of crystallites comprising a first composition comprising lithium, nickel, and oxygen; A grain boundary between adjacent crystallites of the plurality of crystallites, 2 a grain boundary comprising a second composition having a cubic structure, a spinel structure, or a combination thereof; A particle comprising: Particles wherein the concentration of aluminum at the grain boundaries is greater than the concentration of aluminum in the crystallites, and optionally the concentration of cobalt at the grain boundaries is greater than the concentration of cobalt in the crystallites.
2. The particle of claim 1 , wherein said aluminum is substantially uniformly distributed throughout said plurality of particles.
3. 2. The particle of claim 1, wherein the amount of aluminum at the grain boundaries is between 0.01 at% and 10 at% relative to the total transition metals in the first composition.
4. The particle of claim 1 , wherein the concentration of Aluminum in the second composition is less than or equal to the concentration of Co in the second composition.
5. The plurality of crystallites are α-NaFeO 2 5. The particle according to claim 1, having a layered structure, a cubic structure, a spinel structure, or a combination thereof.
6. The crystallites are Li 1+x M.O. 2+y [In the formula, −0.1≦x≦0.3, -0.3≦y≦0.3, 5. The particle of claim 1 , comprising a first composition defined by: M comprises 10 atomic percent or more of nickel.
7. 7. The particle of claim 6, wherein M comprises at least 75 at% atomic percent of nickel.
8. 5. The particle of claim 1, wherein the grain boundaries comprise cobalt in an amount of about 2 at% to about 99 at% relative to the total transition metals in the second composition, and aluminum in an amount of about 0.5 at% to about 99 at% relative to the total transition metals in the second composition.
9. M further comprises an additional metal, said additional metal being present in an amount from about 1 at % to about 90 at %, 7. The particle of claim 6, wherein the additional metal is selected from the group consisting of Mg, Sr, Co, Al, Ca, Cu, Zn, Mn, V, Ba, Zr, Ti, Cr, Fe, Mo, B, and any combination thereof.
10. 7. The particle of claim 6, wherein the crystallites comprise cobalt, and the concentration of the cobalt ranges from 0 at% to about 50 at% relative to the total transition metals in the first composition, and optionally from 1 at% to about 50 at% relative to the total transition metals in the first composition.
11. 7. The particle of claim 6, wherein the crystallites comprise cobalt, and the concentration of the cobalt ranges from 1 at% to about 10 at% relative to the total transition metals in the first composition.
12. the crystallites comprise Mn present in an amount from about 1 at % to about 60 at %; 5. The particle of claim 1, wherein the grain boundary comprises Mn present in an amount of about 1 at% to about 60 at%, where the at% is relative to the total transition metals in the crystallite or grain boundary, respectively.
13. 5. The particle of claim 1, wherein the grain boundaries comprise Ni, Co and Al.
14. 5. The particle according to claim 1, wherein the concentration of Ni at the grain boundary is less than 90 at % relative to the total transition metals at the grain boundary.
15. The particle further includes an outer coating on the surface thereof, the outer coating comprising: Oxides of one or more elements selected from Al, Zr, Y, Co, Ni, Mg, and Li; Fluorides containing one or more elements selected from Al, Zr, and Li; a carbonate comprising one or more elements selected from Al, Co, Ni, Mn, and Li; Sulfates containing one or more elements selected from Al, Co, Ni, Mn, and Li; or Phosphate containing one or more elements selected from Al and Li The particle according to any one of claims 1 to 4, comprising:
16. Li 1+x MO 2+y [In the formula, −0.1≦x≦0.3, -0.3≦y≦0.3, M comprises 80 atomic percent or more of nickel; and a grain boundary between adjacent crystallites of the plurality of crystallites, optionally comprising α-NaFeO 2 a grain boundary comprising a second composition having a layered structure, a cubic structure, a spinel structure, or a combination thereof; wherein a concentration of aluminum at the grain boundaries is greater than a concentration of aluminum in the crystallites, a concentration of cobalt at the grain boundaries is greater than a concentration of cobalt in the crystallites, and the aluminum is substantially uniformly distributed throughout the grain boundaries.
17. 17. The particle of claim 16, wherein the concentration of cobalt at the grain boundaries is greater than the concentration of aluminum at the grain boundaries.
18. the concentration of cobalt in the crystallites is from about 0 to about 17 atomic percent; 17. The particle of claim 16, wherein the concentration of cobalt at the grain boundary is from about 0.5 to about 32 atomic percent, each based on the total transition metal atomic composition of the particle.
19. 17. The particle of claim 16, wherein M further comprises one or more elements selected from the group consisting of Al, Mg, Co, Mn, Ca, Sr, Ba, Zn, Ti, Zr, Y, Cr, Mo, Fe, V, Si, Ga, and B, and wherein the one or more elements are present in the Li layer, the M layer, or both of the crystallites.
20. 17. The particle of claim 16, wherein M comprises 90 percent or greater atomic percent of nickel.
21. 21. An electrochemical cell comprising a cathode active material, the cathode active material comprising particles according to any one of claims 1 to 20.
22. 22. The electrochemical cell of claim 21, characterized by an impedance increase of less than 100% at 4.2 V over 100 cycles at 45°C.
23. 22. The electrochemical cell of claim 21, characterized by an impedance increase of less than 100% at 4.2 V over 200 cycles at 45°C.
24. having an overall composition including lithium, nickel, cobalt, aluminum, and oxygen; primary crystallites having a first composition; A grain boundary between adjacent crystallites of a plurality of crystallites, 2 and a grain boundary comprising a second composition having a cubic structure, a spinel structure, or a combination thereof, the atomic fraction of aluminum to nickel at the grain boundaries is greater than the atomic fraction of aluminum to nickel in the crystallites, and the atomic fraction of cobalt to nickel at the grain boundaries is greater than the atomic fraction of cobalt to nickel in the crystallites; or the atomic fraction of aluminum to nickel at the grain boundaries is greater than the atomic fraction of aluminum to nickel in the overall composition, and the atomic fraction of cobalt to nickel at the grain boundaries is greater than the atomic fraction of cobalt to nickel in the overall composition; or the atomic fraction of aluminum to nickel at the grain boundaries is greater than the atomic fraction of aluminum to nickel in the overall composition, and the atomic fraction of cobalt to nickel in the primary crystallites is less than the atomic fraction of cobalt to nickel in the overall composition; or Combinations of these are called particles.
25. combining a lithium compound and a nickel compound to form a mixture; heat treating the mixture to produce a precursor comprising a plurality of crystallites comprising a first composition comprising Li, Ni, and O, and grain boundaries between adjacent crystallites of the plurality of crystallites; immersing the precursor in a treatment solution containing Co and Al; drying the precursor; and heat treating the precursor to form particles having a higher concentration of aluminum at the grain boundaries than the concentration of aluminum in the crystallites and a higher concentration of cobalt at the grain boundaries than the concentration of cobalt in the crystallites.
5. A method for forming the particles of any one of claims 1 to 4, comprising:
26. 26. The method of claim 25, wherein the liquid is aqueous or comprises an organic solvent, optionally methanol.
27. 26. The method of claim 25, wherein the treatment solution comprises an aluminum amount of 0.01 at% to 10 at% relative to the total transition metals in the precursor particles, and a cobalt amount of 0.5 at% to 10 at% relative to the total transition metals in the precursor particles.
28. 28. The method of any one of claims 25 to 27, wherein the at% Al in the treatment solution is less than or equal to the at% Co in the treatment solution.
29. The plurality of crystallites are α-NaFeO 2 28. The method of any one of claims 25 to 27, wherein the crystalline structure has a layered structure, a cubic structure, a spinel structure, or a combination thereof.
30. The crystallites are Li 1+x M.O. 2+y [In the formula, −0.1≦x≦0.3, -0.3≦y≦0.3, M comprises 10 atomic percent or more of nickel.
31. 31. The method of claim 30, wherein M comprises at least 75 at% atomic percent nickel.
32. M further comprises an additional metal, said additional metal being present in an amount from about 1 at % to about 90 at %; 31. The method of claim 30, wherein the additional metal is selected from the group consisting of Mg, Sr, Co, Al, Ca, Cu, Zn, Mn, V, Ba, Zr, Ti, Cr, Fe, Mo, B, and any combination thereof.
33. 28. The method of any one of claims 25 to 27, wherein the grain boundaries comprise cobalt in an amount between about 2 at% and about 99 at% relative to the total transition metals at the grain boundaries, and aluminum in an amount between about 0.5 at% and about 99 at% relative to the total transition metals at the grain boundaries.
34. An anode; An electrolyte; A cathode; 1. An electrochemical cell comprising: a cathode comprising an electrochemically active cathode material comprising a plurality of particles, the plurality of particles each comprising a plurality of crystallites of a first composition comprising lithium, nickel, and oxygen; A grain boundary between adjacent crystallites of the plurality of crystallites, 2 and a grain boundary comprising a second composition having a cubic structure, a spinel structure, or a combination thereof; the electrochemically active cathode material has an initial discharge capacity of 180 mAh / g or more; An electrochemical cell having an impedance increase of less than 50% at 4.2 V over 100 cycles at 45° C.
35. 35. The cell of claim 34, having an impedance increase of less than 120% at 4.2 V over 200 cycles at 45°C.
36. 35. The electrochemical cell of claim 34, characterized by an impedance increase of less than 50% at 50% state of charge over 200 cycles at 45°C.
37. 35. The cell of claim 34, wherein each of the crystallites comprises lithium, nickel, cobalt, and oxygen.
38. 38. The cell of claim 37, wherein each of the crystallites further comprises Al.
39. 38. The cell of claim 37, wherein each of the crystallites further comprises Mn.
40. 38. The cell of claim 37, wherein each of the crystallites further comprises Mg.
41. 35. The cell of claim 34, wherein the first composition and the second composition have the same elements.
42. The first composition comprises Li 1+x M.O. 2+y [In the formula, −0.95≦x≦0.3, -0.3≦y≦0.3, 42. The cell of any one of claims 34 to 41, wherein M is defined by: M comprises at least 80 atomic percent nickel.
43. 43. The cell of claim 42, wherein M further comprises one or more elements selected from the group consisting of Mg, Sr, Co, Al, Ca, Cu, Zn, Mn, V, Ba, Zr, Ti, Nb, Ta, Cr, Fe, Mo, W, Hf, and B, and wherein said one or more elements are present in the Li layer, the M layer, or both of the crystallites.
44. 43. The cell of claim 42, wherein M comprises 90 percent or greater atomic percent of nickel.
45. 42. The cell of any one of claims 34 to 41, wherein the crystallites comprise cobalt, and the cobalt concentration ranges from 1 at% to about 50 at% relative to the total transition metals of the first composition.
46. 42. The cell of any one of claims 34 to 41, wherein the crystallite comprises cobalt, and the cobalt concentration ranges from 1 at% to about 15 at% relative to total transition metals in the crystallite.
47. 42. The cell of any one of claims 34 to 41, wherein the crystallites comprise Co and Mg.
48. 42. The cell of any one of claims 34 to 41, wherein the second composition comprises Al.
49. 42. The cell of any one of claims 34 to 41, wherein the first composition is free of Al.
50. 42. The cell of any one of claims 34-41, wherein the Al in the second composition is substantially uniformly distributed throughout the plurality of particles.
51. 42. The cell of any one of claims 34 to 41, wherein Al is present at less than 4 atomic percent relative to the total transition metals in the first composition.
Citation Information
Patent Citations
Polycrystalline metal oxide, methods of manufacture thereof, and articles comprising the same
EP2744754A2
Polycrystalline metal oxide, methods of manufacture thereof, and articles comprising the same
JP2017105709A
Positive electrode active material for non-aqueous electrolyte secondary battery, method for producing the same, and non-aqueous electrolyte secondary battery
US20110033750A1
Polycrystalline metal oxide, methods of manufacture thereof, and articles comprising the same
WO2013025328A2
Polycrystalline layered metal oxides comprising NANO-crystals
WO2017189887A1